1990
DOI: 10.1088/0031-9120/25/6/309
|View full text |Cite
|
Sign up to set email alerts
|

Problematical words and concepts in physics education: a study of Papua New Guinean students' comprehension of non-technical words used in science

Abstract: Many of the problems of comprehension experienced by students in physics classes arise not from the technical words used but from the non-technical words used. This paper discusses some of the results of a study conducted in Papua New Guinea on students' comprehension of forty-five non-technical words used in science classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…The truth is, the train is still going on force, only the force is not strong enough to move the train. Different understanding from words between students and teachers can also cause misconceptions (Marshall & Gilmour, 1990). (iii) Humanistic thinking Students often look at things from a human perspective.…”
Section: A Studentsmentioning
confidence: 99%
“…The truth is, the train is still going on force, only the force is not strong enough to move the train. Different understanding from words between students and teachers can also cause misconceptions (Marshall & Gilmour, 1990). (iii) Humanistic thinking Students often look at things from a human perspective.…”
Section: A Studentsmentioning
confidence: 99%
“…For example, in their study of students' comprehension of nontechnical science words, Marshall and Gilmour (1991) found that many New Guinea students in grades 7-12 had a superficial level of understanding for nontechnical words, resulting in an inability to effectively communicate science ideas to others during class. The nontechnical words, words that are not conceptually loaded terms but are used frequently in science textbooks, are words that are rarely addressed instructionally by teachers.…”
Section: Nature Of Science Termsmentioning
confidence: 99%
“…Teachers typically assume that students understand nontechnical words, such as component, consistent, exclude, and interpret. Marshall and Gilmour (1991) concluded that secondary teachers need to determine both the lexical and conceptual knowledge base of their students as they present science information. Moreover, teachers need to pay attention to nontechnical words that may hinder comprehension in science.…”
Section: Nature Of Science Termsmentioning
confidence: 99%
“…A possible exception is a study by Evans and Morrison (2011) showing that Hong Kong first year university students report considerable difficulties in understanding technical vocabulary. On the other hand at the secondary school level, and particularly in science, research has built up a considerable body of evidence to demonstrate that to teach though an L2 requires teachers to think carefully about their explanations of science concepts (Marshall, Gilmour, & Lewis, 1991;Othman & Saat, 2009).…”
mentioning
confidence: 99%